2022
DOI: 10.1039/d2qo00612j
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective and stereospecific synthesis of functionalized 3,4-dihydro-2H-1,4-thiazines by catalyst-free [3 + 3] annulation of pyridinium 1,4-zwitterionic thiolates and aziridines

Abstract: A regioselective and stereospecific [3+3] annulation between pyridinium 1,4-zwitterionic thiolates and aziridines has been developed, allowing the practical and enantio-retained preparation of functionalized 3,4-dihydro-2H-1,4-thiazines. This reaction proceeds smoothly via a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…3,4-Dihydro-2 H -1,4-thiazines ( 170 and 171 ) were prepared via a domino S N 2 ring-opening/ N -Michael addition cyclization/retro-Michael addition/pyridine extrusion procedure under mild conditions without metal mediation or the need for a strong base (Scheme 31). 108…”
Section: Reactions Of Aziridinesmentioning
confidence: 99%
“…3,4-Dihydro-2 H -1,4-thiazines ( 170 and 171 ) were prepared via a domino S N 2 ring-opening/ N -Michael addition cyclization/retro-Michael addition/pyridine extrusion procedure under mild conditions without metal mediation or the need for a strong base (Scheme 31). 108…”
Section: Reactions Of Aziridinesmentioning
confidence: 99%
“…In 2022, Wang and co-workers developed an efficient transformation to achieve the synthesis of 1,4-thiazine derivatives ( 37 and 38 ) (Scheme 8). 30 The reaction proceeded smoothly by mixing pyridinium 1,4-zwitterionic thiolates 1 and 2-aryl-substituted aziridines 36 in CH 3 CN solvent at 80 °C for an hour, which afforded a variety of 3,4-dihydro-2 H -1,4-thiazine derivatives ( 37 and 38 ) in moderate to excellent yields. Mechanistic studies indicated that the transformation involved two reaction pathways.…”
Section: Cyclization Reactions Of Pyridinium 14-zwitterions and Pyrid...mentioning
confidence: 99%
“…Another example of the formal (3 + 3) cyclization of pyridinium 1,4-zwitterions 1 was reported by Chen et al in 2022 ( Scheme 11 ) [ 58 ]. The reaction with both alkyl- and aryl-substituted aziridines provided a wide range of functionalized 3,4-dihydro-2 H -1,4-thiazines ( 42 and 43 ) in good-to-high yields with excellent levels of regioselectivity.…”
Section: Sulfur-based Pyridinium and Quinolinium 14-zwitterionsmentioning
confidence: 99%